2012
DOI: 10.1371/journal.pone.0048507
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC and CaV1.2 in Detrusor Overactivity in a Model of Obesity Associated with Insulin Resistance in Mice

Abstract: Obesity/metabolic syndrome are common risk factors for overactive bladder. This study aimed to investigate the functional and molecular changes of detrusor smooth muscle (DSM) in high-fat insulin resistant obese mice, focusing on the role of protein kinase C (PKC) and Cav1.2 in causing bladder dysfunction. Male C57BL/6 mice were fed with high-fat diet for 10 weeks. In vitro functional responses and cystometry, as well as PKC and Cav1.2 expression in bladder were evaluated. Obese mice exhibited higher body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 53 publications
1
34
1
Order By: Relevance
“…This supports our conclusion that the hypertrophy was generalized over the entire bladder wall. Similar results were found in the STZ-induced type I diabetes rat model (11,27). However, multiple studies suggest that this hypertrophy may be mostly due to diuresis as opposed to diabetes per se (17,27).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This supports our conclusion that the hypertrophy was generalized over the entire bladder wall. Similar results were found in the STZ-induced type I diabetes rat model (11,27). However, multiple studies suggest that this hypertrophy may be mostly due to diuresis as opposed to diabetes per se (17,27).…”
Section: Discussionsupporting
confidence: 80%
“…This neurogenic residual component could be due to activation of P2X receptors not affected by ␣,␤-methylene ATP or PPADS. Other studies have also shown residual components of EFS-induced contractions in diabetic animal models (4,24,27). There was also an increased TTX-resistant component to EFS-induced contraction in diabetic animals.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Fourweek-old male C57BL6/J mice were provided by the Central Animal House Services of State University of Campinas (CEUA-UNICAMP). The animals were housed two per cage on a 12-hour light/dark cycle, and fed for 12 weeks with either a standard chow diet (carbohydrate: 70%; protein: 20%; fat: 10%) or a high-fat diet that induces obesity (carbohydrate: 29%; protein: 16%; fat: 55%) (Leiria et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Animal models have provided evidence to confirm a relationship between metabolic syndrome/hyperlipidemia and OAB symptoms (Rahman et al, 2007;Nobe et al, 2008;Lee et al, 2011;Gasbarro et al, 2010). Obesity-associated insulin resistance has been shown to play an important role in OAB pathophysiology in mice (Leiria et al, 2012).…”
Section: Introductionmentioning
confidence: 96%